Global Uncertainty and Tail Risk in Indonesia’s Islamic and Conventional Equity Markets - Arie Sukma (Management Institute Faculty of Economics Universitas Andalas, 2026)
Is the Indonesian Islamic stock market more resilient to extreme risks compared to conventional markets when global uncertainty increases? Using daily data from the Jakarta Islamic Index (JKII) and the Jakarta Stock Exchange Composite Index (JKSE), we integrate the GARCH–EVT approach, quantile regression, and Expected Shortfall (ES) regression to simultaneously investigate the distribution structure and transmission of global uncertainty shocks. We decompose extreme risk into two main components—the structural thickness of the tail distribution and the realized conditional loss due to volatility dynamics—and show that these two dimensions can lead to different conclusions. Our results indicate that the conventional market has a thicker tail distribution, indicating a higher probability of extreme events. However, after accounting for conditional volatility, the Islamic market exhibits slightly larger average extreme losses. On the other hand, no significant difference is found in sensitivity to global uncertainty between the two markets. Our findings suggest that the difference between Islamic and conventional markets lies in the structure of extreme risk formation, not in the shock transmission mechanism. Our study contributes by demonstrating that tail risk should be understood as the result of the interaction between the distribution of extremes and volatility dynamics in the context of global uncertainty.